A Retrospective Medical Record Review of Utilization Patterns and Medical Resource Use Associated with Repository Corticotropin Injection among Patients with Rheumatologic Diseases in the United States - Nelson, Winnie W. (Rheumatol Ther, 2017)
INTRODUCTION: Repository corticotropin injection (RCI) has anti-inflammatory and immune-modulatory effects and is approved for multiple indications, including several rheumatologic conditions. The aims of this nationally representative, retrospective, observational study were to describe patient characteristics, RCI treatment patterns, and barriers to RCI use in patients with rheumatologic disease, and to compare medical resource use (MRU) before and after RCI therapy. METHODS: A random sample of US physicians was recruited to abstract the medical records of deidentified patients with a diagnosis of rheumatoid arthritis (RA), psoriatic arthritis (PsA), dermatomyositis/polymyositis (DM/PM), or systemic lupus erythematosus (SLE) who had been treated with RCI in the previous 24 months. Patient characteristics and patterns of RCI use were identified. Mean MRU in the 3 months before and after RCI therapy was compared using paired-samples t tests. RESULTS: A total of 449 physicians abstracted the medical records of 217 RA, 190 PsA, 254 DM/PM, and 95 SLE patients. In all groups combined, patients had received a mean of 3.3 treatment medications before initiating RCI. Most patients (75%–94%) were receiving RCI for the first time, indicating that repeated courses of RCI were uncommon. RCI was used as bridge therapy in 18% of patients. Approximately 24% of patients encountered an obstacle in accessing RCI, primarily insurance-related. After RCI therapy, the number of hospitalizations and hospital days were significantly reduced for all cohorts (all P < 0.05), and the number of outpatient visits was significantly lower for all cohorts (P < 0.05) except the SLE cohort (P = 0.3230). Study limitations include potentially incomplete data in the medical records and a relatively short duration for capturing MRU changes. CONCLUSIONS: RCI was used primarily as late-line therapy in patients with rheumatologic diseases. Medical resource use was significantly lower in the 3 months after therapy compared with 3 months prior. This finding suggests that RCI may improve disease control and warrants further evaluation. FUNDING: Mallinckrodt Pharmaceuticals.